Fresno County Bar Association Law Day Luncheon: Attorney General John Van de Kamp - Watkins, Howard::::::::: (1987)
Sandra Snyder speaking at lectern; seated: Legal Services Voluntary Legal Services Program Coordinator Carmen Romero and Debra Kazanjian Snyder and Kazanjian are 1987 Law Day Co-Chairs